Survey of the wheat and derivatives production chain regarding the 2030 Agenda and the SDG - Racowski, Ilana; Amato Neto, João (Sustainability in Debate, 2021)
The adequacy of the 2030 Agenda and the SDG is a new instrument that companies should implement within their innovative processes to improve social, environmental, and economic issues internally and externally. Thus, this work aims to diagnose the wheat and derivatives segment and the adoption/implementation of the 2030 Agenda and SDG to business practices. To this end, a sample of 91 companies of the wheat agribusiness and processing industry was studied, using the survey-based exploratory-descriptive methodology. Data collected underwent qualitative and quantitative analysis, which demonstrated that although many of the SDGs are under assessment for possible new integration with those remaining and those under implementation, the number of objectives already included in business practices is still trivial (38.4%, that is, about 6 out of 17).